2019
DOI: 10.3389/fenrg.2019.00116
|View full text |Cite
|
Sign up to set email alerts
|

Shewanella oneidensis NADH Dehydrogenase Mutants Exhibit an Amino Acid Synthesis Defect

Abstract: Shewanella oneidensis MR-1 is a dissimilatory metal reducing bacterium with a highly branched respiratory electron transport chain. The S. oneidensis MR-1 genome encodes four NADH dehydrogenases, any of which may be used during respiration. We previously determined that a double-knockout of two NADH dehydrogenases, Nuo and Nqr1, eliminated aerobic growth in minimal medium. However, the double-knockout strain was able to grow aerobically in rich medium. Here, we determined that amino acid supplementation rescue… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 40 publications
1
4
0
Order By: Relevance
“…We observed that both the control and NADH dehydrogenase double mutant strain produced ~1 mM 2,3‐butanediol from 10 mM acetoin under this condition (Figure 4A ). In this condition, the NADH dehydrogenase mutant strain produced slightly higher levels of 2,3‐butanediol, possibly due to a build‐up of NADH in the cytoplasm, as previously observed (Duhl & Ter Avest, 2019 ). The 2,3‐butanediol concentration decreased during stationary phase for both strains, possibly due to back conversion to acetoin after major electron donors in the medium were consumed.…”
Section: Resultssupporting
confidence: 81%
See 2 more Smart Citations
“…We observed that both the control and NADH dehydrogenase double mutant strain produced ~1 mM 2,3‐butanediol from 10 mM acetoin under this condition (Figure 4A ). In this condition, the NADH dehydrogenase mutant strain produced slightly higher levels of 2,3‐butanediol, possibly due to a build‐up of NADH in the cytoplasm, as previously observed (Duhl & Ter Avest, 2019 ). The 2,3‐butanediol concentration decreased during stationary phase for both strains, possibly due to back conversion to acetoin after major electron donors in the medium were consumed.…”
Section: Resultssupporting
confidence: 81%
“…We speculate that this was due to a greater amount of stored organic carbon accumulated in the cells during aerobic growth in flasks. The ∆ nuoN ∆ nqrF1 NADH dehydrogenase mutant has a reduced respiration rate which reduces its ability to oxidize residual organic carbon during the aerobic phases of the experiment (Duhl & Ter Avest, 2019 ). It is not likely that cell death was responsible for the lack of acetoin reduction as the strain was capable of elevated electron transfer to fumarate (Figure 2C ), albeit at a reduced rate compared to the hydrogenase mutant.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, with the increase in the NAD(H) pool size, the activities of citrate synthase and pyruvate dehydrogenase (PDH) could be gradually inhibited, thus reducing the energy conversion efficiency. 54,55 In fact, increasing the NAD(H) pool capacity without strengthening the electron flux of the electron transport chain inevitably resulted in the excessive accumulation of intracellular electrons, which may lead to an imbalance in intracellular redox homeostasis and interfere with cellular activities. 150,151 Fig.…”
Section: Enhancement Of Intracellular Releasable Electron Poolmentioning
confidence: 99%
“…However, EET currently proceeds at a low rate due to (i) inefficient energy conversion capacity, [50][51][52] (ii) inadequate intracellular electron generation, [53][54][55][56][57] and (iii) high transmembrane or cell-electrode interfacial electron transfer resistance, [58][59][60][61][62][63] which seriously restrict practical and costefficient application of BESs. Over the last decade, synthetic biology and materials engineering approaches have been adopted to rationalize the design and construction of EET conduits to overcome these deficiencies.…”
Section: Introductionmentioning
confidence: 99%